Pengembangan Modul Praktikum Koloid Berbasis Problem Based Learning Untuk SMA - Alfi Syahar Arrozani; Netti Herawati; Muhammad Jasri Djangi (ChemEdu, 2022)
Development of problem-based learning colloid practicum modules for SMA. Essay. Chemical Education Study Program. Department of Chemistry. Faculty of Math and Science. Makassar State University (supervised by Netti Herawati and Muhammad Jasri Djangi). This research is a development research that aims to produce a problem-based learning practicum module on colloid material that is valid, effective and practical. The subjects of this study were the XI IPA class of SMA Aksara Bajeng with a total of 31 people. The development of a problem-based learning practicum module uses the Plomp development model, consisting of five phases, namely the initial investigation phase, design, realization / construction, evaluation and revision tests, and the implementation phase. The instruments used in this study consisted of validation instruments, student activity observation sheets, practicum module assessment sheets, student response questionnaires and practicum implementation sheets. The results of this study indicate that: (1) The practicum module is declared valid with an average validity value of 3.64, (2) the practicum module is declared effective based on the percentage of participant activity of 96% and the average value of the practicum module is 92.93 with effective category (3) The module is said to be practical based on the results of the student response questionnaire by 71% in the very practical category and 29% in the practical category, and the results of the teacher response questionnaire are 92.5%.